SCHOOL FEEDING PROGRAM AND ITS IMPLICATION ON PUPILS’ RETENTION AND ATTENDANCE IN OYI LOCAL GOVERNMENT AREA OF ANAMBRA STATE NIGERIA - Okadigwe John Chukwujekwu (CV. RADJA PUBLIKA, 2025)
The School Feeding Program (SFP) is a vital initiative aimed at improving the overall well-being of students by providing nutritious meals in schools. This program has significant implications for pupils' retention and attendance, especially in developing regions like Anambra State, Nigeria. Adopting a descriptive survey design, the research aimed to explore the extent to which the SFP influences school enrolment, attendance, academic achievement, and the challenges faced in its implementation. A sample of 148 participants selected from 15 schools through simple random sampling were involved in the study. Data were collected using a validated questionnaire, and the reliability was tested using the Cronbach method. The study found a positive correlation between the school feeding programme and increased school enrolment, improved pupil attendance, and enhanced academic performance. Pupils were more punctual, had better attendance, and showed improvements in both curricular and extracurricular activities. However, challenges such as inadequate funding, poor cooking facilities, insufficient classrooms, and negative parental attitudes were identified as hindrances to the programme’s effective implementation. Based on the findings, the study recommends the provision of adequate funding, the involvement of qualified personnel in planning and evaluation, and the establishment of a monitoring system to ensure the programme’s success. This study contributes to the growing body of literature on the effectiveness of school feeding programmes in promoting educational outcomes in Nigeria and highlights the need for further policy improvements to address the challenges identified.